SERUM ENZYMATIC AND ENDOCRINE PROFILE IN UTERINE TORSION AFFECTED BUFFALOES - PATELIYA, CHINTAN S; PATEL, J A; DHAMI, A J; MADHIRA, S P; SARVAIYA, N P (The Indian Journal of Animal Reproduction, 2023)
This study was conducted to investigate the endocrinal and enzymatic alterations in buffaloes suffering from uterine torsion (Gr-I, n=10) in comparison to normal parturient buffaloes Gr-II, n=6) just before as well as 1 hr, 1 day and 1 week after parturition. Serum enzymatic profile revealed that the mean values of serum AST and CPK were significantly higher in torsion affected buffaloes than normal parturient buffaloes at all peripartum intervals, whereas, the mean values of serum ALT were found significantly (p<0.05) elevated in affected buffaloes only during prepartum period. Serum endocrine profile revealed apparently lower serum estradiol 17β concentrations in uterine torsion affected than normal parturient buffaloes at most periparturient periods, whereas circulatory progesterone and cortisol levels were significantly higher in torsion affected buffaloes than normal ones, before and 1 hr after parturition only.